Cytotoxic Effect of Saffron Stigma Aqueous Extract on Human Transitional Cell Carcinoma and Mouse Fibroblast - Feizzadeh, Behzad; Tavakkol Afshari, Jalil; Rakhshandeh, Hassan; Rahimi, Alireza; Brook, Azam; Doosti, Hassan (Urology Journal, 2008)
Introduction: Saffron has been suggested to have inhibitory effects on tumoral cells. We evaluated the cytotoxic effect of aqueous extract of saffron on human transitional cell carcinoma (TCC) and mouse non-neoplastic fibroblast cell lines. Materials and Methods: Human TCC 5637 cell line and mouse fibroblast cell line (L929) were cultivated and incubated with different concentrations of aqueous extract of saffron stigma (50 mg/mL to 4000 mg/mL). Cytotoxic effect of saffron was evaluated by morphologic observation and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide colorimetric assay after 24, 48, 72, and 120 hours in each cell line. Results: After 24 hours, morphological observations showed growth inhibitory effects at saffron extract concentrations higher than 200 µg/mL for L929 cells and at concentrations of 50 µg/mL to 200 µg/mL for the TCC cells. These changes became more prominent after 48 hours. However, significant growth inhibitory effects of the extract were shown at concentrations of 400 µg/mL and 800 µg/mL. Higher concentrations of saffron correlated inversely with cell population of both cell lines. Significant reduction of the survived cells was seen at concentrations of 400 µg/mL and 2000 µg/mL for TCC and L929 cell lines, respectively. After 120 hours, decrease in the percentage of survived cells at higher concentrations of saffron extract was seen in both cell lines. At a concentration of 800 mg/mL, the survived L929 cells plummeted to less than 60% after 120 hours, while no TCC cells survived at this time. No L929 cells survived at 2000 mg/mL. Conclusion: Saffron aqueous extract has inhibitory effects on the growth of both TCC 5637 and normal L929 cell lines. This effect is dose dependent.